GE_GERICHTE P/9352/2019 vom 13. März 2020 - GE Cour de justice (2020)
PLAINTE PÉNALE;DÉLAI;INFRACTION CONTRE L'HONNEUR;DÉNONCIATION CALOMNIEUSE;EXCUSABILITÉ | CPP.310; CP.31; CP.173; CP.174; CP.177; CP.303; CP.14